Dual band bandpass filters with full band reflectionless response and enhanced upper stopband suppression - Gangxiong Wu; Yang Jin; Wei Zhang; Ruirui Jiang; Jin Shi (Scientific Reports)
Abstract This paper presents a novel dual-band bandpass filter (BPF) with two-port all-frequency reflectionless characteristics and enhanced upper-band suppression. The design integrates a square ring resonator (SRR) and advanced coupled lines (CLs), incorporating complementary absorptive branches to achieve broadband reflectionless performance. To mitigate upper-band harmonics, radial-stub-loaded resonators (RSLSs) with high-impedance transmission lines (HITLs) are introduced, extending suppression up to 10f 0 without significantly increasing the circuit footprint. A comprehensive theoretical analysis, including parametric studies and transmission zero (TZ) derivation, is conducted to optimize performance. Two prototypes are designed, fabricated, and tested: Prototype I achieves dual-band operation with all-frequency absorption, while Prototype II further enhances harmonic suppression. Experimental results closely align with simulations, with Prototype I exhibiting 3-dB fractional bandwidths (FBWs) of 19.5% and 9.7% at 1.38 GHz and 2.63 GHz, respectively, with insertion losses (ILs) of 0.95 dB and 1.47 dB. Prototype II achieves superior harmonic suppression, with attenuation levels of 22.8 dB over 2.9–20 GHz and 28.5 dB within 3.0–12 GHz. These designs offer high selectivity, inter-band isolation exceeding 45 dB, and full-spectrum absorption, providing an efficient solution for modern RF and wireless communication systems.